Begonia noraaunorae (section Petermannia, Begoniaceae) a new species endemic to Surigao del Sur, Mindanao Island, Philippines - Blasco, Freddie A.; Tandang, Danilo N.; Alejandro, Grecebio Jonathan D.; Bucay, Mark Angelo C.; Cortes, Junelito C.; Rubite, Rosario R. (Phytotaxa, 2023)
Begonia noraaunorae is described as a new species endemic to the Philippines from the limestone forest of Surigao del Sur. It grows on limestone rocks in semi-shaded broadleaf forest along a national highway. B. noraaunorae resembles B. negrosensis in having erect stems and obovately oblong leaves with sparse hairs and an acuminate apex, but differs in having shorter stems, larger leaves with light green patches, and capsules longer than wide (vs. wider than long), without large bracteoles directly beneath (vs. with), on longer peduncles. The new species is named after Nora Aunor, National Artist for Film and Broadcast Arts. Based on IUCN criteria, B. noraaunorae is considered Vulnerable.